2020
DOI: 10.18502/pbr.v6i(s1).4400
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Phosphate Metabolism and Gender-based Phenotypic Analysis in Healthy Subjects’ Urine Following Oral Administration

Abstract: Background: Chloroquine, 4-N-(7-chloroquinolin-4-yl)-1-N,-N-diethylpentane-1,4-diamine has promising activity against corona virus disease 2019 (COVID-19) and as such, it is imperative to thoroughly understand and determine the rate at which individual body systems metabolizes the drug. Chloroquine a known antimalarial drug belongs to the chemical class of 4-aminoquinolines. Objectives: The study aimed to analyze Chloroquine and its metabolite in biological fluids of healthy subjects by simple thin layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…[ 2 , 3 , 4 , 5 ] It has been suggested as a potential anticancer drug, [6] and for treatment of COVID‐19. [ 1 , 7 , 8 ] Several studies suggested that interactions of chloroquine with DNA might underlie the antimalarial activity of CQP. [6] …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[ 2 , 3 , 4 , 5 ] It has been suggested as a potential anticancer drug, [6] and for treatment of COVID‐19. [ 1 , 7 , 8 ] Several studies suggested that interactions of chloroquine with DNA might underlie the antimalarial activity of CQP. [6] …”
Section: Introductionmentioning
confidence: 99%
“…This is important to reach at decisions whether malaria developed resistance to this medication and alternative solutions. [ 4 , 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although diarrhea is present in approximately 20-25% of patients infected with MERS-Cov or SARS-Cov, intestinal symptoms have rarely been reported in patients with COVID-19 (Sahin, Erdogan & Agaoglu, 2020) [66] . Various studies have been conducted to identify drug candidates to combat the virus, from natural and synthetic sources, with different individuals metabolizing such drugs in diverse manners as results of their genetic makeup (Bunu et al, 2020) [15] . For the meantime, some persons believe that consuming herbal medicines or medicinal plants that act as immunomodulators can prevent or even cure COVID-19 infection (Nugraha et al, 2020) [57] .…”
Section: Introductionmentioning
confidence: 99%